Theories and Research Methodologies for Design-Based Implementation Research: Examples from Four Cases. Issue 14 (December 2013) - Russell, Jennifer Lin; Jackson, Kara; Krumm, Andrew E.; Frank, Kenneth A.
This chapter reviews four projects that reflect the principles of design-based implementation research (DBIR) in an effort to highlight a range of relevant theoretical and methodological perspectives and tools that can inform future work associated with DBIR.